Simultaneous bonding and forming of Mg fibre metal laminates at high temperature. (December 2021) - Ghiotti, Andrea; Bruschi, Stefania; Kain, Martin; Lizzul, Lucia; Simonetto, Enrico; Tosello, Guido
Abstract: The transport industry is increasingly demanding structural parts having higher strength-to-weight ratio and the use of Fibre Metal Laminates (FML) represent a potential solution to overcome the limits of traditional material categories in terms of impact and fatigue resistance. The paper presents a new process chain to manufacture magnesium alloy-based FML parts by simultaneous forming and bonding of different material layers at high temperature. The effects of different surface preparation and thermal treatment of the metal layers are investigated, and FLM samples obtained by means of different process routes have been tested by Lap-shear, T-peel and tensile tests. The results demonstrate how a combination of sandblasting and annealing treatments allows to obtain FLM with an interlayer maximum stress respectively of 1.23 and 11.07 MPa along the normal and tangential directions. Then a new exponential traction-separation law is proposed to model the delamination phenomena. Finally, both the proposed process chain and model are validated on the basis of a hat profile part, that was formed and tested. The results demonstrate the possibility to integrate the bonding and forming steps in a single operation, and to model the bonding zone mechanical behaviour. Highlights: Novel process chain to manufacture magnesium alloy based FMLs parts by simultaneous forming and bonding at high temperature Bonding characterization by means of lap-shear and T-peel tests as a function of the surface state New exponential traction-separation proposed to model the bonding layer, implemented in the process numerical model Industrial trials validated both the new process chain as well as the proposed exponential traction-separation law